CHARACTERISTICS OF SELECTED MANGKALIHAT COALS ACCORDING TO PETROGRAPHIC AND PROXIMATE ANALYSES - BINARKO SANTOSO; NINING S. NINGRUM (Indonesian Mining Journal, 2010)
A carbonate complex in the Mangkalihat area, East Kalimantan, has been selected for this study, because this area has some coal deposits associated with dominant limestone intercalated by thin claystone and sandstone. Commonly, most Indonesian coals were formed in fluvial and deltaic depositional environment. Accordingly, this study is interesting due to the depositional environment of the coals in association with a marine condition. This environment mostly results in relatively high mineral matter and sulphur contents, particularly pyrite in this study; brighter lithotype and dominant vitrinite content over liptinite and inertinite. The geologic factors have clearly proven a good correlation among the results of megascopic, microscopic and proximate analyses. The coals with brighter lithotype, high vitrinite and moisture contents were formed under a wetter marsh environment. On the other hand, the duller lithotypes with the presence of inertinite and mineral matter were deposited in a dryer marsh environment. The presence of high pyrite and sulphur contents strongly indicates a marine incursion during the coal forming in this area.